Online Customer Experience, Segmentation, Targeting, Positioning, and Coffee Shop Business Competitiveness Model - Patwayati, Patwayati; Titing, Andry Stepahnie (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to explore how Online Customer Experience, Segmentation, Targeting, and Positioning are interpreted and implemented by coffee shop owners in building business competitiveness. This study uses a qualitative approach with a descriptive design to gain an in-depth understanding of the experiences, strategies, and meanings that business owners build in their daily practices. Informants were selected using purposive sampling, involving five coffee shop owners who were directly engaged in business management, customer service, digital promotion, target market determination, and brand image development. Data were collected through semi-structured in-depth interviews and direct observation. Data were analyzed using a descriptive qualitative procedure consisting of data reduction, data display, and conclusion drawn. The findings reveal that Online Customer Experience plays an important role in shaping initial customer perceptions through digital platforms, especially social media. Segmentation is practiced intuitively based on customer lifestyle and visit behavior. Targeting is focused on dominant customer groups such as students, young workers, and local communities, with price, menu, and atmosphere adjustments. Positioning is developed through concept differentiation, product uniqueness, and customer experience to create a distinctive business identity. The study concludes that business competitiveness in coffee shops is formed through the integration of these four elements, which collectively support customer attractiveness, business sustainability, and differentiation in a competitive market. This research contributes by offering a qualitative understanding of the coffee shop business competitiveness model based on digital experience and market strategy.